A tale of two Germanias - Peter Hatlebakk (Sjuttonhundratal)
Tacitus’ Germania was translated into Danish twice in the 1790s, first by the historian and jurist Gustav Ludvig Baden (1764–1839) in 1795, and then by his father, the professor of rhetoric Jacob Baden (1735–1805) in 1797. Both translations can be understood as part of a sustained effort to introduce Tacitean and other concepts from classical literature to enrich philosophical reasoning in the vernacular.